THE UNEQUAL ENFORCEMENT OF LIBERALIZATION: EVIDENCE FROM RUSSIA'S REFORM OF BUSINESS REGULATION. Issue 4 (24th July 2013) - Yakovlev, Evgeny; Zhuravskaya, Ekaterina
Abstract We document the unequal enforcement of liberalization reform of business regulation across Russian regions with different governance institutions, which leads to unequal effects of liberalization. National liberalization laws were enforced more effectively in subnational regions with more transparent government, a more informed population, a higher concentration of industry, and stronger fiscal autonomy. As a result, liberalization had a substantial positive effect on the performance of small firms and the growth of the official small business sector in regions with stronger governance institutions. In contrast, in regions with weaker governance institutions, we observe no effect of reform and, in some cases, even a negative effect.